The International Pressure Ulcer Prevalence™ Survey: 2006-2015: A 10-Year Pressure Injury Prevalence and Demographic Trend Analysis by Care Setting - VanGilder, Catherine; Lachenbruch, Charlie; Algrim-Boyle, Corrine; Meyer, Stephanie (Journal of wound, ostomy, and continence nursing, 2017)
Measurement of pressure injury (PI) prevalence allows benchmarking within and across facilities; the International Pressure Ulcer PrevalenceTM (IPUP) Survey includes a variety of care settings. The purpose of this study is to present 10 years of US prevalence and limited demographic data (2006-2015) by care setting. Facilities volunteer to participate in the IPUP Survey. Internal clinical teams collect data during a predetermined 24-hour period that includes pressure injury prevalence, demographics, and other pertinent clinical information. Aggregate data was analyzed for this study. The sample for this study was 918,621 patients in the United States; data collection spanned 2006 to 2015. The overall prevalence (OP) of PI in all facilities declined from 13.5% (2006) to 9.3% (2015). Facility-acquired prevalence (FAP) declined from 6.2% (2006) to a range of 3.1% to 3.4% (2013-2015). Acute care OP was 13.3% in 2006 and declined to a range of 8.8% to 9.3% (2012-2015). Facility-acquired prevalence in acute care declined from 6.4% (2006) to 2.9% in 2015, with 2008-2009 showing the most aggressive decline. Long-term acute care (LTAC) had the highest OP at 32.9% in 2006; it declined to 28.8% in 2015. The LTAC-FAP was 9.0% in 2006; it declined to 5.6% in 2015. Recently, the long-term care (LTC) FAP rose from 3.8% in 2013 to 5.4% in 2015. The rehabilitation facility FAP was 2.6% to 2.8% over the last 3 years. Average patient age declined in all care settings with the exception of LTAC and LTC. Braden Scale risk scores remained constant and weight increased in all care settings with the exception of LTC. The OP and FAP in acute care and rehabilitation have declined significantly over this 10-year period. Analysis of OP and FAP in LTC and LTACs varied without any clear-cut directional trends. General facility demographic trends indicate that mean patient age has decreased, Braden Scale scores for pressure injury risk has remained constant, and weight has increased in most care settings.VIDEO ABSTRACT available for more insights from the authors (see Supplemental Digital Content 1, http://links.lww.com/JWOCN/A37).